2016
DOI: 10.1002/stem.2524
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Transplantation Blockade of TNF-α-Mediated Oxygen Species Accumulation Protects Hematopoietic Stem Cells

Abstract: Hematopoietic stem cell (HSC) transplantation (HSCT) for malignancy requires toxic preconditioning to maximize anti-tumor effects and donor-HSC engraftment. While this induces bone marrow (BM)-localized inflammation, how this BM environmental change affects transplanted HSCs in vivo remains largely unknown. We here report that, depending on interval between irradiation and HSCT, residence within lethally irradiated recipient BM compromises donor-HSC reconstitution ability. Both in vivo and in vitro we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 51 publications
(66 reference statements)
4
23
0
2
Order By: Relevance
“…We supported this assumption by demonstrating that the isolation and cryopreservation of BM grafts more efficiently preserves different HSPCs than those of the BM of an irradiated animal, at least during the first 24 h after lethal TBI. This result is in concordance with a recent report by Ishida et al ( 32 ) who showed that elevated tumor necrosis factor alpha (TNF-α) levels in inflamed BM contribute to the compromised reconstitution of donor BM. However, such a direct comparison between in vivo and a vial containing BM frozen to −80°C is complex considering the number of influencing variables involved.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We supported this assumption by demonstrating that the isolation and cryopreservation of BM grafts more efficiently preserves different HSPCs than those of the BM of an irradiated animal, at least during the first 24 h after lethal TBI. This result is in concordance with a recent report by Ishida et al ( 32 ) who showed that elevated tumor necrosis factor alpha (TNF-α) levels in inflamed BM contribute to the compromised reconstitution of donor BM. However, such a direct comparison between in vivo and a vial containing BM frozen to −80°C is complex considering the number of influencing variables involved.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, the reconstituted hematopoiesis post AL-BMT showed a shift toward the myeloid lineage, and the M-bias was strongly evident in the mice that received the BM collected 8 h after the induction of hypometabolism. A recent study suggested that the transfer of LT-HSCs pretreated with an antioxidant, N -acetyl cysteine, led to myeloid reconstitution ( 32 ). The M-bias observed in this study could partially be explained by considering that SJNP-1, which was used for inducing HMS, is an effective free radical scavenger and antioxidant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports suggest that TNFα acts on HSPCs to promote their maintenance in the steady state and engraftment during regeneration 31 , 35 , 36 . Other reports suggest that TNFα acts on HSPCs to inhibit their function during homeostasis and that TNFα-receptor blockade prior to transplantation promotes HSPC survival 37 , 38 . Our results support the notion that TNFα has pro-regenerative effects on HSPCs.…”
mentioning
confidence: 99%
“…Evi1 [28] , Tie2 [24] 等标记. 这种利用特异基因标记的方法 [19] . 实验操作中可 根据实际照射源的类型(钴60或者X-ray)以及小鼠的耐 受程度和实验的可操作性等方面协调进行.…”
unclassified